Thermodynamic properties of binary alloys from monte carlo simulations - 임상호; G. E. Murch; W. A. Oates; M. Hasebe (TAYLOR & FRANCIS, 1990)
The relations between the thermodynamic properties of the unary lattice gas and the equivalent binary substitutional and interstitial alloys are discussed. New methods for the estimation of the partial particle energy in a lattice gas from Monte Carlo simulations in both the petit and grand canonical ensembles are presented and evaluated. Taken together with well established procedures for estimating the particle chemical potential and more recent procedures for estimating the lattice gas pressure, it becomes possible, for the first time, to obtain reliable determinations of both the partial and integral quantities for internal energy, entropy and free energy at a given temperature and composition in a rigid binary alloy from the one Monte Carlo experiment in either ensemble. Some illustrative results are given for the square lattice with nearest neighbour interactions. ？ 1990 Taylor & Francis Ltd.